Chemical composition and antibacterial activity of essential oils from Citrus aurantifolia leaves and fruit peel against oral pathogenic bacteria - RAIANE S. LEMES; CASSIA C.F. ALVES; ELISÂNGELA B.B. ESTEVAM; MARIANA B. SANTIAGO; CARLOS H.G. MARTINS; TAINÁ C.L. DOS SANTOS; ANTÔNIO E.M. CROTTI; MAYKER L.D. MIRANDA (Anais da Academia Brasileira de Ciências)
ABSTRACT Tooth decay is a major public health problem which affects a large number of people in several countries. Even though more than 700 bacterial species have been detected in the oral cavity, Streptococcus and Lactobacillus stand out as the genera that cause tooth decay and other periodontal diseases. In this study, essential oils from Citrus aurantifolia leaves (CL-EO) and fruit peel (CP-EO) were obtained by hydrodistillation by a Clevenger-type apparatus whereas their chemical composition was analyzed by gas chromatography-flame ionization detector (GC-FID) and gas chromatography-mass spectrometry (GC-MS). Limonene (77.5 %), linalool (20.1 %), citronellal (14.5 %) and citronellol (14.2 %) were the main constituents found in the essential oils from C. aurantifolia leaves and fruit peel. Antibacterial activity of essential oils was evaluated in terms of its minimum inhibitory concentration (MIC) values by the broth microdilution method in 96-well microplates. Both CL-EO and CP-EO displayed some activity against all oral pathogens under investigation; MIC values ranged from 20 to 200 µg/mL. CL-EO and CP-EO not only had promising activity against Streptococcus mutans (MIC = 20 µg/mL) and Lactobacillus casei (31.25 µg/mL), but also displayed antibacterial activity against all studied cariogenic bacteria. Efficacy of essential oils against S. mutans and L. casei is noteworthy and should be further investigated.